Pengembangan Usaha Kopi Roasting Di Desa Siempat Rube II Kecamatan Siempat Rube Kabupaten Pakpak Bharat - Dian Agustina Dalimunthe; Erli Mutiara; Khaerul Saleh; Mentari Arisyid Mulyadi; Amalia Akita (Universitas Sebelas Maret, 2025)
Coffee is one of the leading commodities that has high economic value, especially in Indonesia which is known as one of the best coffee producers in the world. This community service program aims to increase production, financial management, marketing and partner income. The method of implementing activities is through training in the use of coffee roasting machines, starting from selecting quality coffee beans, roasting techniques that produce the best taste, to coffee product marketing strategies. This Community Service Partner is the Ochi Coffee Business in Siempat Rube II Village, Pakpak Bharat, North Sumatra. The results of this community service activity can increase partner production, namely coffee production using a roasting machine, partners can market coffee through online media, financial management is getting better and partner income is increasing. Mentoring is also carried out continuously to ensure the success of the program. The conclusion of this community service is that the community service activity runs smoothly and well, partner income is increasing and production costs are decreasing with the presence of a coffee roasting machine. Kopi merupakan salah satu komoditas unggulan yang memiliki nilai ekonomi tinggi, terutama di Indonesia yang dikenal sebagai salah satu penghasil kopi terbaik di dunia. Program pengabdian masyarakat ini bertujuan untuk meningkatkan produksi, manajemen keuangan, pemasaran dan pendapatan mitra. Metode Pelaksanaan kegiatan melalui pelatihan penggunaan mesin roasting kopi, mulai dari pemilihan biji kopi yang berkualitas, teknik roasting yang menghasilkan cita rasa terbaik, hingga strategi pemasaran produk kopi. Mitra Pengabdian ini adalah Usaha Ochi kopi di Desa Siempat Rube II Pakpak Bharat Sumatera Utara. Hasil dari kegiatan pengabdian ini dapat meningkatkan produksi mitra yaitu produksi kopi menggunakan mesin roasting, mitra dapat memasarkan kopi melalui media online, manajemen keuangan semakin baik dan pendapatan mitra semakin meningkat. Pendampingan juga dilakukan secara berkelanjutan untuk memastikan keberhasilan program. Simpulan pengabdian ini adalah kegiatan pengabdian berjalan dengan lancar dan baik, pendapatan mitra semakin meningkat dan biaya produksi semakin berkurang dengan adanya mesin roasting kopi.